2010
DOI: 10.1111/j.1445-5994.2010.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing liver transplantation waiting list mortality: a report from the Australian National Liver Transplantation Unit, Sydney

Abstract: Despite the increasing proportion of donor offers being used, the waiting list mortality is increasing. A solution to this problem is an increase in organ donation to keep pace with the escalating demand for LTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The mean waiting time for DDLT was 35.81±29.18 days, which was substantially shorter than previous reports [21], [22]. In mainland China, health insurance does not cover liver transplantation [23], [24].…”
Section: Discussionmentioning
confidence: 81%
“…The mean waiting time for DDLT was 35.81±29.18 days, which was substantially shorter than previous reports [21], [22]. In mainland China, health insurance does not cover liver transplantation [23], [24].…”
Section: Discussionmentioning
confidence: 81%
“…[1][2][3] The median pretransplantation waiting time among active wait-listed adult patients increased from 12.9 months in 2009, to 17.6 months in 2010, to 18.5 months in 2011. 2 In an effort to expand available organs for liver transplantation, many transplant centers are looking beyond the traditional "ideal" donor, to include the use of marginal or extended criteria donor organs, including the use of grafts from older donors.…”
mentioning
confidence: 98%
“…Age was a significant predictive factor only after the implementation of MELD scoring. Age has previously been described as an independent risk factor for mortality in patients with cirrhosis in several studies 29‐32. Most authors have reported a higher risk for patients more than 50 years old 33‐36.…”
Section: Discussionmentioning
confidence: 97%